Впровадження концепції “ЗЕЛЕНЕ БУДІВНИЦТВО” у КНУБА - Четверіков, Ю. В. (Ways to Improve Construction Efficiency, 2014)
In the article are presented the principal conception of Green Building end its main elements, international experience on working out end using the systems certification of buildings to be in accordance with criterions of Green Building, experience of realization the conception of Green Building in KNUBA.